2018
DOI: 10.1016/j.advwatres.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Determining water storage depletion within Iran by assimilating GRACE data into the W3RA hydrological model

Abstract: Link to publication record in Explore Bristol Research PDF-document This is the author accepted manuscript (AAM). The final published version (version of record) is available online via Elsevier at https://www.sciencedirect.com/science/article/pii/S0309170817306322?via%3Dihub#! . Please refer to any applicable terms of use of the publisher. University of Bristol -Explore Bristol Research General rightsThis document is made available in accordance with publisher policies. Please cite only the published version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 46 publications
(2 reference statements)
3
31
0
Order By: Relevance
“…In recent years, a number of studies have reported on efforts to optimize GRACE‐DA performance by investigating (1) the spatial scales of assimilation (Eicker et al, ; Schumacher et al, ), (2) the representation of horizontal error covariance of models and GRACE observations (Forman & Reichle, ; Khaki et al, ; Khaki, Schumacher, et al, ), (3) the choice of GRACE products and scaling factors (Kumar et al, ; Schumacher et al, ), and (4) the choice of data assimilation techniques (Girotto et al, ; Khaki et al, ; Khaki, Hoteit, et al, ; Schumacher et al, ). Despite these efforts, challenges persist, particularly for regions that have substantial TWS depletion.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of studies have reported on efforts to optimize GRACE‐DA performance by investigating (1) the spatial scales of assimilation (Eicker et al, ; Schumacher et al, ), (2) the representation of horizontal error covariance of models and GRACE observations (Forman & Reichle, ; Khaki et al, ; Khaki, Schumacher, et al, ), (3) the choice of GRACE products and scaling factors (Kumar et al, ; Schumacher et al, ), and (4) the choice of data assimilation techniques (Girotto et al, ; Khaki et al, ; Khaki, Hoteit, et al, ; Schumacher et al, ). Despite these efforts, challenges persist, particularly for regions that have substantial TWS depletion.…”
Section: Introductionmentioning
confidence: 99%
“…Here we choose to test both AUKF and Kalman‐Takens filters to improve upon model simulations between 2003 and 2013 over Iran (32.4279°N, 53.6880°E). The rationale behind choosing Iran for this synthetic analysis, and not Australia, is that a remarkable water storage decline is reported over this region, mainly due to anthropogenic impacts, which cannot be detected by W3RA (see Khaki, Forootan, Kuhn, Awange, van Dijk, et al, ). A major part of the negative water storage trend is due to human impacts (see details in ; Forootan et al, ; Khaki, Forootan, Kuhn, Awange, van Dijk, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The rationale behind choosing Iran for this synthetic analysis, and not Australia, is that a remarkable water storage decline is reported over this region, mainly due to anthropogenic impacts, which cannot be detected by W3RA (see Khaki, Forootan, Kuhn, Awange, van Dijk, et al, ). A major part of the negative water storage trend is due to human impacts (see details in ; Forootan et al, ; Khaki, Forootan, Kuhn, Awange, van Dijk, et al, ). Synthetic observations are produced using the WaterGAP Global Hydrology Model (WGHM; Döll et al, ; Müller Schmied et al, ) monthly TWS outputs, which contain the anthropogenic impacts (Khaki, Forootan, Kuhn, Awange, van Dijk, et al, ), at two different spatial resolution of 1° × 1° and 3° × 3°.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations